Meet the lords. - Stirzaker, Tim; Stirzaker, Tim; Giles, James (Television producer and director); Giles, James (Television producer and director); Bevan, Gillian, 1956- (Academic Video Online, 2017)
Inside the gilded halls of the House of Lords - at the heart of the UK government - the Lords face contentious bills, eccentric traditions, bubbling tensions, and a fight for their future. Meet the Lords provides an insider's glimpse into an astonishing world full of bizarre rules and age-old traditions. This is a world where staff carry swords and peers still dress in ermine-trimmed red robes for grand ceremonies. Tensions build as the Lords face up to the government, the public and each other. What lies in store for the House of Lords? Will reformists succeed in overhauling the system or will the traditionalists win out in the end? Brexit hits the Lords with a bang when they vote on leaving Europe and become the centre of the nation's attention. They also have their biggest ceremonial day of the year when the Queen pays her annual visit. Lords turn out in massive numbers to have their say on the most important issue in decades and decide whether to rebel on Brexit or not. And on Queen's Speech day, there are ermine gowns to put on and ancient traditions to follow, but Her Majesty's impending arrival isn't exciting Lord Foulkes, who feels it is an irritating distraction. The House's Victorian sewage system is on its last legs and not equipped to deal with so many Lords. To fix the many structural problems an inquiry is considering a dramatic move for the five or so years the work will take. Some Lords have radical overhaul plans of their own and want the size of the House cut. And Baroness D'Souza is worrying about peers who claim their expenses without contributing and has some new research. Over the course of a year, Meet the Lords, the exclusive behind-the-scenes documentary, follows some of the larger than life characters that inhabit the House of Lords, one of Britain's oldest, most idiosyncratic and important institutions. For the first time, free-roaming cameras have been allowed to film inside the Lords Chamber and in its committees to capture moments that matter to the UK, but usually go unseen. Featuring new people's peers, hereditaries and political grandees as they try to change or influence legislation, it follows their personal passions and clashes with the government, all in a gothic palace where centuries-old ceremony and tradition still dominate proceedings.